Relationship between estimating glomerular filtration rate and cerebral large artery stenosis: a secondary analysis of a cross-sectional study - Song, Ran; Kong, Yan; Liu, Su-Juan; Li, Wen-Chao; Li, Qiang; Yan, Ming-Huan (Frontiers in Medicine, 2026)
BackgroundLarge cerebral artery stenosis (LCAS) is a risk factor for ischemic stroke; however, its relationship with kidney function remains unclear. This study aims to explore the association between glomerular filtration rate (eGFR) and LCAS.MethodsThis is a secondary analysis of a cross-sectional study, with data from 1,011 asymptomatic South Korean adults aged ≥45 years with cardiovascular disease risk factors or stroke family history, recruited from the Neurology Clinic or Health Management Center at CHA Bundang Medical Center in Seoul, between March 2008 and December 2014. The independent variable was eGFR, calculated using the CKD-EPI 2009 creatinine-based equation, and the dependent variable was large cerebral artery stenosis (LCAS), defined as ≥50% stenosis or occlusion of intracranial or extracranial cerebral arteries (or both), assessed by MRA. Multivariable logistic regression was used to evaluate the association between eGFR and LCAS, adjusting for demographic factors, cardiovascular risk factors, and biochemical markers. A generalized additive model (GAM) was used to assess the dose-response relationship between eGFR and LCAS. Stratified analysis and interaction tests were conducted to evaluate the eGFR-LCAS relationship.ResultsHigher eGFR levels were independently associated with lower odds of LCAS. After adjusting for confounding factors, each 1 mL/min/1.73 m2 increase in eGFR was associated with a 1% reduction in LCAS risk (OR = 0.99, 95% CI: 0.98–1.00). Compared to the lowest tertile (T1), the highest tertile (T3) was associated with a 39% lower risk of LCAS (OR = 0.61, 95% CI: 0.39–0.96). In subgroup analyses, the association was statistically significant in women (OR = 0.98, 95% CI: 0.96–0.99; P = 0.009) and in statin users (OR = 0.97, 95% CI: 0.95–0.99; P = 0.015). However, the interaction was borderline for sex (P interaction = 0.051) and not significant for statin use (P interaction = 0.105), and these subgroup findings should be interpreted as exploratory.ConclusionThese findings indicate an association between eGFR and LCAS in this cohort. Subgroup patterns and clinical implications require confirmation in prospective and external cohorts. Kidney function may serve as a risk marker; whether it should inform screening strategies requires confirmation. These findings are derived from a South Korean population with cardiovascular risk factors and require validation in diverse populations and general population settings.